Crystal‐Plastic Deformation in Seismically Active Carbonate Fault Rocks. Issue 4 (31st March 2021) - Ohl, Markus; Nzogang, Billy; Mussi, Alexandre; Wallis, David; Drury, Martyn; Plümper, Oliver
Abstract: The spatial separation of macroscopic rheological behaviors has led to independent conceptual treatments of frictional failure, often referred to as brittle, and viscous deformation. Detailed microstructural investigations of naturally deformed carbonate rocks indicate that both frictional failure and viscous mechanisms might operate during seismic deformation of carbonates. Here, we investigate the deformation mechanisms that were active in two carbonate fault zones in Greece by performing detailed slip‐system analyses on data from automated crystal‐orientation mapping transmission electron microscopy and electron‐backscatter diffraction. We combine the slip‐system analyses with interpretations of nanostructures and predictions from deformation mechanism maps for calcite. The nanometric grains at the principal slip surface should deform by diffusion creep but the activation of the (0001)< 1 ¯ 2 1 ¯ 0> slip system is evidence for a contribution of crystal plasticity. A similar crystallographic preferred orientation appears in the cataclastic parts of the fault rocks despite exhibiting a larger grain size and a different fractal dimension, compared to the principal slip surface. The cataclastic region exhibits microstructures consistent with activation of the (0001)< 1 ¯ 2 1 ¯ 0> and 10 1 ¯ 4< 2 ¯ 021> slip systems. Postdeformational, static recrystallization, and annealing produce an equilibrium microstructure with triple junctions and equant grain size. We propose that repeated introduction of plastic strain and recrystallization reduces the grain size and offers a mechanism to form a cohesive nanogranular material. This formation mechanism leads to a grain‐boundary strengthening effect resulting in slip delocalization which is observed over 6 orders of magnitude (μm‐m) and is expressed by multiple faults planes, suggesting cyclic repetition of deformation and annealing. Key Points: Crystal‐plastic deformation occurred in seismically deformed carbonate rocks Deformation and annealing produce a grain‐boundary strengthening effect Repeated cyclic repetition of deformation and recrystallization leads to formation of a nanogranular material